IMPLEMENTASI INFORMATION AND COMMUNICATION TECHNOLOGIES (ICT) SEBAGAI ALAT PENGAMBILAN KEPUTUSAN DALAM PERENCANAAN ORGANISASI - Syahrul Ramadhan Dalimunthe; Muhammad Irwan Padli Nasution (CV. ADIBA AISHA AMIRA, 2025)
This research aims to explore the role of Information and Communication Technology (ICT) in decision making in organizations and its impact on society. In the era of globalization, ICT has become an essential need that influences various aspects of life, including economic, social and cultural. The method used in this research is qualitative with a descriptive approach, which allows researchers to explore phenomena in depth through collecting data from various sources, such as books and websites. The research results show that ICT plays an important role in providing fast access to relevant data, which supports more precise and information-based decision making. Apart from that, this research also emphasizes the importance of improving the quality of human resources so that they can utilize technology optimally in the decision-making process